Cephalofacial characteristics of the Akan people in the Assin Districts in Central Region of Ghana: Anthropometric Studies - Kyei, Gordon; Moshkdanian, Ghazaleh; Pasbakhsh, Parichehr; Abolhasani, Farid; Rastegar, Tayebeh; Hassanzadeh, Gholamreza (Journal of Contemporary Medical Sciences, 2020)
Objective: Cephalic and facial indices are very important in the classification and identification of populations. The present study aims at determining the cephalic and facial indices among the Akan ethnic group living the Assin Districts in the Central Region of Ghana. Methods: A total of 100 (50 males and 50 females) Akan volunteer adults between the age of 20 and 58 years were recruited for the study. Cephalic Length (CL), Cephalic Width (CW), Facial Width (FW) and Total Facial Height (TFH) were measured using a Spreading caliper. Cephalic Index (CI) [(CW/CL) × 100] and Facial Index (FI) or Prosopic Index (PI) [(TFH/FW) ×100] as well statistical analysis such as z-test and Pearson Correlation were performed. The p value of less than 0.05 was considered statistically significant. Results: Our results are comparable with other authors with mean (for both male and females) CI and FI of 78.6± 4.66 and 96.51 ± 12.55, respectively. There was a correlation between CW and FW as well as some other cephlaofacial parameters. There was no sexual dimorphism of both CI and FI. The predominant head type among the study populations was mesocephalic and brachycephalic while Hyperleptoprosopic was the face type. Conclusion: This study provides baseline data for the Akan people of The Assin Districts of the Central Region of Ghana, which will be valuable in cephalometric anthropometry and in forensic science.